10-Gbps visible light communication in a 10-m free space based on violet series-biased micro-LED array and distance adaptive pre-equalization - Jin, Zuxin; Yan, Lintao; Zhu, Shijie; Cui, Xugao; Tian, Pengfei (Optics letters, 2023)
In this paper, we fabricated a 3×3 violet series-biased micro-LED array with high-output optical power and applied it in high-speed and long-distance visible light communication. By employing the orthogonal frequency division multiplexing modulation scheme, distance adaptive pre-equalization, and a bit-loading algorithm, record data rates of 10.23 Gbps, 10.10 Gbps, and 9.51 Gbps were achieved at 0.2 m, 1 m, and 10 m, respectively, below the forward error correction limit of 3.8×10 . To the best of our knowledge, these are the highest data rates achieved by violet micro-LEDs in free space and the first communication demonstration beyond 9.5 Gbps at 10 m using micro-LEDs.